Checklist of the false scorpions (Arachnida: Pseudoscorpiones) of Colombia, with new records and a key to the identification of the families - Romero-Ortiz, Catalina; García, Fabian; Villarreal, Eduardo (Zootaxa, 2019)
Colombia is a mega-biodiverse country and rich in ecosystems as different as the Amazon and the Andes. Much is known of the vertebrate fauna, however there is still an information-gap for many arthropod groups including the arachnids. Here, we compile all the information available for pseudoscorpions (Arachnida: Pseudoscorpiones) recorded from Colombia and include several new records and distribution extensions. For each described species, we present information on taxonomic history, type localities, global and local distributions, repository of Colombian specimens, and collection numbers when available. We document 12 families, 45 genera and 65 species of pseudoscorpions for Colombia and most species belong to the families Chernetidae (27 species) and Olpiidae (8 species). We record Beierolpium venezuelense Heurtault, 1982, Geogarypus amazonicus Mahnert, 1979, Sathrochthonius venezuelanus Muchmore, 1989, and Semeiochernes armiger (Balzan, 1892) for the first time for Colombia. We further extend the known ranges of Parachernes melonopygus Beier, 1959 and Paratemnoides nidificator (Balzan, 1888). The data suggest that the Caribbean region of Colombia has the highest number of records. Total numbers are not complete and many other new pseudoscorpion species are expected.